2000
DOI: 10.1177/135245850000600303
|View full text |Cite
|
Sign up to set email alerts
|

1H MRSI comparison of white matter and lesions in primary progressive and relapsing-remitting MS

Abstract: Objective-To compare brain metabolite levels in patients with primary progressive (PP) and relapsing remitting (RR) MS and controls. Hypotheses: (1) creatine (Cr), a putative marker of gliosis, is elevated and N-acetylaspartate (NAA), a putative marker of axonal density and functional integrity, is reduced in PPMS lesions and normal appearing white matter (NAWM) compared to control white matter; (2) The pattern of metabolite change in PPMS is different than in RRMS.Methods-MRI and proton magnetic resonance spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
48
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 40 publications
12
48
1
Order By: Relevance
“…In both cases, the estimate of the median is higher for PPMS patients. This finding is supported by earlier work that identified indicators of increased gliosis and axonal loss in PPMS lesions relative to RRMS lesions (Suhy et al, 2000). …”
Section: Resultssupporting
confidence: 87%
“…In both cases, the estimate of the median is higher for PPMS patients. This finding is supported by earlier work that identified indicators of increased gliosis and axonal loss in PPMS lesions relative to RRMS lesions (Suhy et al, 2000). …”
Section: Resultssupporting
confidence: 87%
“…NAA:Cr ratio in CB has been proposed as an index of axonal damage and/or dysfunction for more than a decade 16 as creatine concentration was found to be relatively constant in both lesions and NAWM of MS patients, 17 18 although others have detected increased creatine. 19 Several studies have found reduced NAA:Cr and concentration of NAA in MS lesions, NAWM, and whole brain [20][21][22] of RR and SP patients, but only a few investigators evaluated PP specifically. 12 19 23 In our study, the mean T2LL of all PP patients was 5.09 cm 3 (ranging from 0.62 to 24.77 cm 3 ), representing <2% of the CB ROI volume used to derive NAA:Cr ratios (table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Suhy et al72 compared metabolite levels in PPMS (n=15) and RRMS (n=13) patients with those of controls (n=20). Cr in NAWM of PPMS patients was higher compared to controls (P=0.035), and RRMS patients (P=0.038).…”
Section: Application Of Mrs To Msmentioning
confidence: 99%